Torque magnetometry in YBa2Cu3O7-Î´ single crystals using high sensitive micromechanical torsional oscillator - Perez-Morelo, D.; Pastoriza, H. (IOP Publishing, 2014)
Fil: Perez-Morelo, D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina